Heterogeneity of deletions involving RB-1 and the D13S25 locus in B-cell chronic lymphocytic leukemia revealed by fluorescence in situ hybridization1 - Stilgenbauer, Stephan; Leupolt, Elke; Ohl, Sybille; Weiß, Gunther; Schröder, Martin; Döhner, Konstanze; Bentz, Martin; Lichter, Peter; Döhner, Hartmut (Cancer research, 1995)
Recently, the D13S25 locus, which is in close proximity to the retinoblastoma gene (RB-1) on chromosome band 13q14, was discussed to play a role in the pathogenesis of B-CLL. In the present study, we isolated two overlapping genomic DNA clones (termed c13S25) containing the D13S25 DNA segment and used them as probes to analyze 85 B-CLL cases by fluorescence in situ hybridization; of the 55 cases with two RB-1 copies, 13 exhibited hemizygous (n = 7) or homozygous (n = 6) deletion of D13S25. Of 29 cases with hemizygous deletion of RB-1, all but two also showed loss of D13S25 (hemizygous, n = 25; homozygous, n = 2). One case had a homozygous deletion of both loci. We conclude that deletion of D13S25 occurs in a substantial number of B-CLL without deletion of RB-1. However, in some cases there is deletion of RB-1 without loss of D13S25, suggesting that D13S25 is not the locus of the putative tumor suppressor gene. According to our data, such a gene is most likely located within the genomic region between D13S25 and RB-1.
Gesehen am 07.11.2024